From The Wizard of Oz to The Wizard that W(Oz): Greek adaptations of the famous fairy tale - Τζιτζιλή, Ειρήνη (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2016)
Τhe children’s fairy tale The Wonderful Wizard of Oz was written by L. Frank Baum in 1900 and illustrated by W. W. Denslow. It has been reprinted numerous times since then, most often under the name The Wizard of Oz. After the well-known 1902 Broadway musical and the 1939 film adaptation, the popularity of this book skyrocketed. Since the tale’s first appearance, there have been countless written and illustrated versions for children all over the world. It is remarkable not only that this book stood the test of time for over a century, but that it is still subject to new treatments in addition to being a source of inspiration for developing interactive systems, as well. One way to achieve this goal was by using the methodology of the so-called “Wizard of (W)Oz studies”. This essay examines two contemporary Greek adaptations for young children, and compares them with the “pre-text” of Baum’s original work. My aim is to attempt a comparative narrative analysis and to investigate the ways in which the story has changed and developed in different illustrative types through intertextuality. I will endeavour to determine how the original text was altered and adjusted to young Greek audiences, and how that process of adaptation was influenced by the cultural, social and ideological components of its time.